2020
DOI: 10.2147/imcrj.s243405
|View full text |Cite
|
Sign up to set email alerts
|

<p>Adamantinomatous Craniopharyngioma in an Adult: A Case Report with NGS Analysis</p>

Abstract: Purpose: Several recent studies have documented CTNNB1 and BRAF mutations which are mutually exclusive for adamantinomatous craniopharyngioma (ACP) and papillary craniopharyngioma (PCP) tumors. This discovery is helpful in the development of novel targeted therapies in successful clinical trials with BRAF mutations in PCP cases. However, no such targeted therapy is available yet for ACP. Here, we report novel mutations, which are not previously reported, in a case of an adult ACP using NGS analysis. Results: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 78 publications
1
15
1
Order By: Relevance
“…This SNP is located in the same exon as the R132 mutations and has been reported previously in other types of cancer such as gliomas, glioblastomas, brain tumors, astrocytoma, craniopharyngioma and acute myeloid leukemia in pediatric and adult population, and has been associated with a negative prognosis in some of these neoplasms (Accetta et al, 2018; Acquaviva et al, 2018; Jastania et al, 2020; Soyer et al, 2017; X. W. Wang et al, 2013). The influence of SNP on the enzyme function had been associated with an increase in mRNA‐level expression, affecting intracellular NAPH levels (Acquaviva et al, 2018; Komar, 2007).…”
Section: Discussionmentioning
confidence: 55%
“…This SNP is located in the same exon as the R132 mutations and has been reported previously in other types of cancer such as gliomas, glioblastomas, brain tumors, astrocytoma, craniopharyngioma and acute myeloid leukemia in pediatric and adult population, and has been associated with a negative prognosis in some of these neoplasms (Accetta et al, 2018; Acquaviva et al, 2018; Jastania et al, 2020; Soyer et al, 2017; X. W. Wang et al, 2013). The influence of SNP on the enzyme function had been associated with an increase in mRNA‐level expression, affecting intracellular NAPH levels (Acquaviva et al, 2018; Komar, 2007).…”
Section: Discussionmentioning
confidence: 55%
“…The HBL tumor of this study exhibited exon 25 and exon 9 mutations in ALK and FGFR3 genes (Table 3 ); however, mutations in exon 29 and exon 16 in these two genes were previously reported in an atypical-choroid plexus papilloma (a-CPP) tumor [ 21 ]. In the ALK gene, exon 25 contained a c.3750T>G; p. (Ile1250Met) mutation in the HBL tumor in the present study, and another variant (COSM10044698) was reported at this site, c.3748 A>G; p. (Ile1250Val).…”
Section: Discussionmentioning
confidence: 80%
“…Details of histopathological and immunological methods were published by us previously [ 20 , 21 ]. The formalin-fixed paraffin-embedded (FFPE) tumor tissue used in this NGS analysis was obtained from the Al-Noor Specialty Hospital, Makkah.…”
Section: Case Presentationmentioning
confidence: 99%
“…ACPs are extremely rare in adults, with most adult cases presenting over 50 years of age [9,10]. As the distribution of these tumors follows a bimodal curve, the age at diagnosis for our patient makes this case even more unique.…”
Section: Discussionmentioning
confidence: 89%